Candida Skull Base Osteomyelitis: a Case Report and Literature Review - Krishnamoorthy, Madhusudhan; Othman, Nik Adilah Nik; Hassan, Nor Eyzawiah Binti; Hitam, Shahrul Bin (Acta medica (Hradec Kralove), 2020)
Skull base osteomyelitis (SBO) also commonly known as malignant otitis externa was first described by Meltzer and Kelemen in 1959. Prior to the advent of the antibiotic era, this disease carried a poor prognosis with significant morbidity. It often proved fatal with mortality rates as high as 50%. Commonly seen in the immunocompromised patients, diabetes mellitus is an important associated comorbidity in the pathophysiologic development of this disease. Treatment is instituted by medical therapy with surgery having a limited role. Surgical intervention has a limited role, for example, in fungal SBO. Such cases may require local debridement and intraoperative tissue biopsies for histopathologic confirmation. This is to demonstrate fungal invasion into the skull base, as well as to exclude other sinister differential diagnoses like squamous cell carcinoma of temporal bone. In this case report, we present a rare case of candida SBO and the literature review.
Keywords: Candidiasis; Antifungal Agents; fungal; Osteomyelitis; Skull Base; flukonazol; lidé; Fluconazole; Otitis Externa; osteomyelitida; Anti-Bacterial Agents; otitis externa; osteomyelitis; Male; Diabetes Complications; baze lební; lidé středního věku; mužské pohlaví; antibakteriální látky; komplikace diabetu; antifungální látky; candida; skull base; Middle Aged; kandidóza; Humans